Nilai-Nilai Kemerdekaan Dalam Al-Qur’an Tafsir Qs. An-Nisa’ 4:75 - Muhammad Miftah Irfan (Sekolah Tinggi Agama Islam Nahdlatul Ulama Madiun, 2024)
Islam is a revolutionary movement that has been waiting for centuries. His anti-oppressive spirit was always a topic of conversation for the polytheists at that time. So, it is not surprising that the prophet's struggle in spreading this teaching, of course, faced many obstacles. Unfortunately, after the death of the prophet, the struggle of the Muslims in fighting for the mustad'afin was no longer continued by his successors. The Islamic struggle has now turned into an individual or group struggle. Call it the constant theological debate, or the power struggles that often lead to murder. It is clear that this is not the goal of Islam which the prophet strived for at the risk of his body and soul. The Islam that the prophet fought for was an Islam that liberated, not conquered. In this article, the author will return to the understanding of Islam based on the values ​​of independence, through the interpretation of Qs. An-Nisa '4:75. With this article, the author tries to contribute to the development of an Islamic society.